Incidence of surgical site infection following open hernioplasty and comparison of infection rate among ventral & groin hernia repairs at a THQ hospital Lahore: a single surgeon experience - Sidra Dil Muhammad,; Muhammad Saad Faisal,; Mohammad Akmal Shafiq,; Muhammad Rizwan Saeed, (Journal of the Pakistan Medical Association, 2023)
Objective: To determine the incidence of surgical site infection following open hernioplasty, and to compare the infection rate among ventral and groin hernia repairs. Method: The retrospective study was conducted from April 2 to November 30, 2021, at the Government Tehsil Headquarter Hospital Sabzazar, Lahore, Pakistan, and comprised data form June 2018 to December 2020 of patients with ventral abdominal and groin hernia. All patients underwent hernioplasty by a single consultant surgeon and were discharged within 2 days of surgery. Surgical-site infections were recorded on follow-up visits up to 30 days of operation, and were compared between ventral and groin hernia cases. Data was analysed using SPSS 22. Results: Of the 218 patients with mean age 37.07±4.94 years, 117(53.67%) were males, 108(49.54%) smokers and 127(58.25%) hypertensive, while 110(50.45%) had ventral abdominal hernia and 108(49.54%) had groin hernias. Mean operative time and mean hospital stay were 56.53±6.20 minutes and 3.06±1.31days, respectively. Mean wound drainage in abdominal hernia cases was 8.99±2.02 days. Surgical site infection incidence following open hernioplasty was 2(0.91%). Infection rate among ventral abdominal and groin hernioplasty were 1(0.90%) and 1(0.92%) (p=0.50). Conclusion: Incidence of surgical site infection following open hernioplasty showed no significant difference between ventral abdominal and groin hernia repairs. Key Words: Surgical site infection, Hernioplasty, Groin hernia.